Cross-cultural effects of COVID-19 on higher education learning and teaching practice: A case study from Greece - Kefalaki, Margarita; Nevradakis, Michael; Li, Qing (Journal of University Teaching and Learning Practice, 2021)
COVID-19 has greatly impacted all aspects of our everyday lives. A global pandemic of this magnitude, even as we now emerge from strict measures such as lockdowns and await the potential for a ‘new tomorrow’ with the arrival of vaccines, will certainly have long-lasting consequences. We will have to adapt and learn to live in a different way. Accordingly, teaching and learning have also been greatly impacted. Changes to academic curricula have had tremendous cross-cultural effects on higher education students. This study will investigate, by way of focus groups comprised of students studying at Greek universities during the pandemic, the cross-cultural effects that this ‘global experience’ has had on higher education, and particularly on students in Greek universities.The data collection tools are interviews and observations gathered from focus groups.Keywords: Cross-cultural effects; COVID-19; international students; higher education teaching and learning; global education; higher education; online education.